A dynamic collision avoidance solution scheme of unmanned surface vessels based on proactive velocity obstacle and set-based guidance - Wenming, Wang; Jialu, Du; Yihan, Tao (Ocean engineering, 2022)
This paper proposes a proactive velocity obstacle (PVO) method through pre-judging whether there are collision risks between an unmanned surface vessel (USV) and its obstacle vessels according to the predicted motion states of the USV by its motion mathematical model to optimize the collision avoidance decision-making. Then integrating the proposed PVO method and the line of sight (LOS) algorithm into the set-based guidance (SBG) framework, we create a dynamic collision avoidance (DCA) solution scheme of USVs and carry out simulations in the cases of single vessel and multiple vessels encounter, respectively. The USV-DCA solution scheme can make the USV successfully avoid obstacle vessels while complying with the international regulations for preventing collisions at sea (COLREGs) and follow the desired path without collisions. The simulation results show that the USV-DCA solution scheme based on PVO and SBG can make USVs avert a series of small velocity changes and make a safer collision avoidance decision than the original SBG framework scheme in the multiple vessels encounter case, which verifies the effectiveness and superiority of our proposed USV-DCA solution scheme. •Propose the PVO method to optimize the collision avoidance decision-making.•Create a USV-DCA solution scheme by integrating the PVO method and the LOS method into the SBG framework.•USV-DCA makes the USV avert a series of small velocity changes and makes a safer collision avoidance decision.•USV-DCA makes the USV follow the desired path without collision while complying with COLREGs.